POTENTIAL DIVERSITY OF WATER ORGANISM AND WATER QUALITY OF THE LEBAK LEBUNG SWAMP ECOSYSTEM FOR FISHERIES IN RANTAU BAYUR DISTRICT, BANYUASIN REGENCY - Aisyah Fatriani; Hilda Zulkifli; Mochamad Syaifudin; Mohammad Rasyid Ridho; Dade Jubaedah (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2022)
The abundance and diversity of aquatic organism and fish in Lebak Lebung Kemayan and Lebak Lebung Tudakan in Rantau Bayur District and their relationship to water quality in both of Lebak Lebung were researched in November 2021. The method used in determining the sampling location was